2001
DOI: 10.1111/j.1572-0241.2001.04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of progression in Barrett's esophagus II: baseline 17p (p53) loss of heterozygosity identifies a patient subset at increased risk for neoplastic progression

Abstract: Patients with 17p (p53) LOH are at increased risk for progression to esophageal adenocarcinoma as well as high-grade dysplasia, increased 4N, and aneuploidy. 17p (p53) LOH is a predictor of progression in Barrett's esophagus that can be combined with a panel of other validated biomarkers for risk assessment as well as intermediate endpoints in prevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(157 citation statements)
references
References 72 publications
9
147
0
1
Order By: Relevance
“…both), 51 and loss of heterozygosity for 17p, 52 further implicating the p53 tumor suppressor gene in the molecular pathogenesis of esophageal adenocarcinoma. 39 With further validation, it is likely that such biomarkers (in particular, cell nuclear DNA content or ploidy) soon will be incorporated into routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…both), 51 and loss of heterozygosity for 17p, 52 further implicating the p53 tumor suppressor gene in the molecular pathogenesis of esophageal adenocarcinoma. 39 With further validation, it is likely that such biomarkers (in particular, cell nuclear DNA content or ploidy) soon will be incorporated into routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, aneuploidy and LOH at chromosome 17p defined patients at high risk for developing EAC in prospective trials, respresenting Phase 4 biomarker development studies (Teodori et al, 1998;Barrett et al, 1999;Rabinovitch et al, 2001;Reid et al, 2001). In addition, inactivation of p16 was shown to be an early and frequent event in EAC (Suzuki et al, 1995;Barrett et al, 1996Barrett et al, , 1999Maley et al, 2004).…”
Section: Runx3 Mrna Expression Runx3 Msp Value (Nmv)mentioning
confidence: 99%
“…For example, loss of heterozygosity (LOH) at chromosome 17p (17p-LOH) and ploidy status define the risk of developing EAC in prospective trials (Teodori et al, 1998;Barrett et al, 1999;Rabinovitch et al, 2001;Reid et al, 2001). Aneuploid subclones were detectable prior to the p53 inactivation (Neshat et al, 1994;Galipeau et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In a large, prospective trial of patients with Barrett esophagus, 17p LOH in biopsy tissues was found to predict cancer progression at 5 years. 79 Moreover, p53 antibodies have been detected in the sera of Barrett patients who later progressed to dysplasia and cancer. 80 Studies investigating the prognostic significance of 17p LOH and p53 antibodies in gastric cardia tumors have not been done.…”
Section: Resistance Of Growth-inhibitory Signalsmentioning
confidence: 99%